A Sequential Homologation of Alkynes and Aldehydes for Chain Elongation with Optional 13C‐Labeling. Issue 8 (20th January 2016) - Brunner, Andreas; Hintermann, Lukas
Abstract: Terminal alkynes (RCCH) are homologated by a sequence of ruthenium‐catalyzed anti‐Markovnikov hydration of alkyne to aldehyde (RCH2 CHO), followed by Bestmann–Ohira alkynylation of aldehyde to chain‐elongated alkyne (RCH2 CCH). Inverting the sequence by starting from aldehyde brings about the reciprocal homologation of aldehydes instead. The use of 13 C‐labeled Bestmann–Ohira reagent (dimethyl ((1‐ 13 C)‐1‐diazo‐2‐oxopropyl)phosphonate) for alkynylation provides straightforward access to singly or, through additional homologation, multiply 13 C‐labeled alkynes. The labeled alkynes serve as synthetic platform for accessing a multitude of specifically 13 C‐labeled products. Terminal alkynes with one or two 13 C‐labels in the alkyne unit have been submitted to alkyne–azide click reactions; the copper‐catalyzed version (CuAAC) was found to display a regioselectivity of >50 000:1 for the 1, 4‐ over the 1, 5‐triazine isomer, as shown analytically by 13 C NMR spectroscopy. Abstract : Really stretching it : "True" homologations for either terminal alkynes or aldehydes are provided by a sequence of ruthenium‐catalyzed anti‐Markovnikov hydration of terminal alkynes to aldehydes, followed by Bestmann–Ohira alkynylation of aldehydes to alkynes (see scheme). The reaction opens a general access to 13 C‐labeled linear targets, which, in the case of alkynes, can serve as starting materials for alkyne–azide " 13 Click" reactions.